Engine emissions and poisoning effect of synthetic oil's additives on catalytic converter using an engine dynamometer - Kaleli, H (EMERALD, 2003)
Two 5W-30 synthetic-base phosphorus containing (commercial) and phosphorus-free (P-free) crankcase oils were tested for engine performance characteristics, engine emissions and poisoning effects of oil additives on a three-way catalytic converter using engine dynamometer. The emission data of the two oils taken during engine operation were compared in the absence and presence of the catalytic converter. Surface characterization was used to determine the poisoning catalyst effect accumulated from the oil additives in the ceramic washcoat. Oil analyses were also used to examine the condition of the lubricant occurred during engine performance testing operation. The experimental engine performance tests indicated that the catalytic converter diminished the torque and power for the commercial and P-free oils, whereas the specific fuel consumption increased for both oils in the presence of the catalytic converter.
Keywords: oils; engines; emissions; CRANKCASE OIL; PHOSPHORUS; Engineering